2008
DOI: 10.1254/jphs.sc0070405
|View full text |Cite
|
Sign up to set email alerts
|

Species Difference in the Contribution of T-Type Calcium Current to Cardiac Pacemaking as Revealed by R(−)-Efonidipine

Abstract: Abstract. The contribution of the T-type Ca 2+ current to cardiac pacemaking was examined in isolated right atrial tissue from the mouse, guinea pig, and rabbit using a specific blocker, R(−)-efonidipine. At 10 −6 M, R(−)-efonidipine produced negative chronotropy, which was prominent in the mouse and small but significant in the guinea pig. No effect was observed in the rabbit. Microelectrode recordings revealed that R(−)-efonidipine significantly prolongs the pacemaker (phase 4) depolarization of the sinoatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…* The arrhythmias and toxicity seen in the mouse cell assay indicate that the mouse cardiac cells are more sensitive to T-type Ca 2 + channel blockade than human cells, which is in agreement with the findings by Tanaka et al, who demonstrated that the contribution of T-type Ca 2 + current to cardiac pacing is much greater in the mouse than in larger species. 33 Future Directions…”
Section: The Stem Cell Assaymentioning
confidence: 99%
“…* The arrhythmias and toxicity seen in the mouse cell assay indicate that the mouse cardiac cells are more sensitive to T-type Ca 2 + channel blockade than human cells, which is in agreement with the findings by Tanaka et al, who demonstrated that the contribution of T-type Ca 2 + current to cardiac pacing is much greater in the mouse than in larger species. 33 Future Directions…”
Section: The Stem Cell Assaymentioning
confidence: 99%
“…N‐type Ca 2+ channels are localized at the nerve endings in the sympathetic and central nervous systems, which regulate the release of neurotransmitters [22–24]. T‐type Ca 2+ channels may be associated with the gradual depolarization phase of the sinus nodal action potential [25], which appears only in smaller animals [26,27].…”
Section: The Relationship Between Sympathetic Nerve Activity and Ca2+mentioning
confidence: 99%
“…The RMP of USMCs of around −55 mV is close to the voltage level for the window current from I CaT (Blanks et al, 2007 ). However, experimental studies in cardiac SAN cells illustrate that maneuvres designed to reduce I CaT result in alterations of SAN APs (Hagiwara et al, 1988 ; Masumiya et al, 1998 ; Tanaka et al, 2008 ). In our study, modest reduction of I CaT hyperpolarizes the USMC model RMP and diminishes the bursting spikes with a mild effect on the SAN model cell AP.…”
Section: Discussionmentioning
confidence: 99%